A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary - Winkler, Daniel (Zootaxa, 2016)
The genus Lepidocyrtus was previously represented by 17 species in Hungary, including four species with locus typicus in this country. Opportunistic sampling in mid-mountain grassland and forest habitats resulted in records of several species from the L. lignorum group and allowed to describe the new species L. traseri sp. nov. The L. lignorum group, established and named after the eponymic species, is composed by a total of 11 species. The main characteristics shared by every species in this group are the dorsal body macrochaetotaxy R0R1R2/00/0101+3 and the presence of scales on the antennae and legs. The new species is close to L. lignorum (Fabricius, 1793) and L. violaceus (Geoffroy, 1762) but differs from them by the color pattern, number of interocular scales, type of labral papillae and the number of inner setae on the manubrial plate. An identification key is given for differentiating all species of this group.